A new 3D print technology filament 100% based in natural biological sources and cork waste - Vieira, Flávia A. (2020)
Lately, there is an increasing demand for natural and sustainable materials, which contributes to the natural appealing of cork uses. Cork industry produces around 30 % wt of residues in powder form. The main goal of this work is to use cork as reinforcing phase in a maize starch thermoplastic (TPS) matrix producing a cork-polymer composite (CPC) from 100 % natural sources. The starch thermoplastic matrices were produced using three different weight proportions of starch. Cork powders with granulometries ranging from 63μm-80μm were considered. The moisture absorption was evaluated during 16 weeks in a shelf-life storage experiment. The morphological characteristics were performed by SEM images and chemical profile by spectrometric and thermal analysis. Both TPS and CPC formulations were characterized in terms of moisture absorption. All infrared spetra were pre-treated and analyzed under multivariate statistics. The samples with lower moisture absorption and best group of results for chemical and morphological characterization were selected for further mechanical tests and 3D filaments production.